ABOUT A NEW CREATION OF MONUMENTS – IN SEARCH OF NON-EXISTENT VISION OF PAST IN CENTRAL-EASTERN EUROPE - Korpała, Małgorzata (Porównania, 2015)
After the reclaim of independence by countries of the Central-Eastern Europe, the issue of protection of monuments became a part of the new historic and national rhetoric. This article shows examples of the reconstruction and creation of monuments after 1989 year in Poland, Lithuania and Ukraine. New contemporary ideas are encoded in the monuments and subsequently they become important factors shaping present day economy, society and nations. Reconstructions after 1989 have to be interpreted as the realisation of contemporary politics adorned with historic symbols. Interventions in the architecture of the monuments result from the need to restore the lost heritage to much fuller glory than had even existed before its destruction.